Book Review: Commercial Law - Koh, Philip Tong Ngee (Journal of Malaysian and Comparative Law, 2019)
The writer, R.M. Goode, is the Crowther Professor of Credit and Commercial Law and Director of the Centre for Commercial Law Studies at Queen Mary College, University of London. His previous major works were on the Law on Hire-Purchase and more recently on areas of Credit and Security. This recent work by the learned writer is a major undertaking spanning eight years and exhibits all the erudite learning one has learnt to expect from the pen of Professor Goode. The publicity blurb on the cover of the book claims for the description of being "the most up-to-date, comprehensive book on the theory, and practice of commercial transactions". This review will not attempt a detail comment on the text but a broad survey of its major features.